Genomic and phenotypic characterization of Enterococcus faecalis from broiler sternal bursitis: antimicrobial resistance and one health risks - Jessica Ribeiro; Vanessa Silva; Pedro Pinto; Madalena Vieira-Pinto; Rita Batista; Alexandra Nunes; João Paulo Gomes; Gilberto Igrejas; Lillian Barros; Sandrina A. Heleno; Filipa S. Reis; Patrícia Poeta (Veterinary Research Communications, 2026)
Enterococcus spp. are opportunistic bacteria capable of acquiring antimicrobial resistance and virulence traits, facilitating their adaptation to multiple ecological niches. Sternal bursitis, a condition affecting poultry welfare and carcass quality, remains poorly characterized from a microbiological perspective. This study provides the first genomic and phenotypic characterization of Enterococcus isolates from bursitis lesions in broilers, aiming to assess their antimicrobial resistance profiles, virulence determinants, and genetic diversity within a One Health framework. A total of 44 Enterococcus isolates were recovered from 48 sternal bursitis lesions, all identified as E. faecalis . Resistance was common for tetracycline (70.5%) and erythromycin (27.3%), while all isolates remained susceptible to critically important antimicrobials, including vancomycin and linezolid. Whole-genome sequencing revealed a genetically diverse population, comprising multiple sequence types, plasmid replicons, and virulence gene profiles, including determinants for adhesion, biofilm formation, capsule synthesis, and extracellular proteases. Ionophore resistance genes ( narA , narB ) were also detected in several lineages. The coexistence of antimicrobial resistance and virulence determinants, often linked to mobile genetic elements, highlights the potential of lesion-associated with E. faecalis to act as reservoirs of relevant genes with zoonotic implications. Overall, this work highlights the diverse and ecological role of Enterococcus in extraintestinal poultry infections, reinforcing the need for continued genomic surveillance to promote animal health, food safety, and antimicrobial stewardship.

In vivo evaluation of the anti-inflammatory efficacy of liposomes loaded with Echinacea purpurea roots extracts - Sara F. Vieira; Diana Fonseca-Rodrigues; Daniel Mendanha; Vânia I. B. Castro; Ricardo A. Pires; Rui L. Reis; Filipa Pinto-Ribeiro; Helena Ferreira; Nuno M. Neves (Drug Delivery and Translational Research, 2026)
WHO ranked chronic inflammatory diseases as the most significant cause of death. The current therapeutic approach is the constant administration of clinically available anti-inflammatory drugs; however, this strategy presents severe side effects. New entities derived from plants have shown their potential for developing safe and effective therapies. Particularly, Echinacea purpurea extracts have demonstrated strong anti-inflammatory properties. Therefore, dichloromethanolic extracts of E. purpurea roots (DE-R), rich in alkylamides, were used to produce an anti-inflammatory formulation. To increase therapeutic efficacy, DE-R were loaded into liposomes (LPs), which were also engineered to actively target M1 macrophages via surface functionalization with folic acid (FLPs). The developed formulations were homogeneous, with a mean particle size of ≈114 nm. The liposomes were cytocompatible at all tested concentrations and strongly reduced IL-6 production in LPS-stimulated macrophages. As expected, FLPs + DE-R were 6.3 times better than LPs + DE-R, and 9.7 times greater than free DE-R. The anti-inflammatory activity of free DE-R and DE-R-loaded FLPs was assessed in an experimental rat model of inflammation. A single intra-articular injection of the FLPs + DE-R promoted a significant reduction of edema, inflammatory pain, and immune cell infiltration, particularly of CD68 + macrophages, as well as IL-6 expression. This formulation reduced synovial inflammation more efficiently than free DE-R. We also demonstrated that the developed formulation was safe, as no welfare changes or harmful toxicity to major organs were observed. Therefore, E. purpurea roots extracts loaded in liposomes can be used as a natural, innovative, and powerful new formulation to treat chronic inflammatory diseases. Graphical Abstract

Bioaccessibility and prebiotic effect of apple pomace: A promising new functional ingredient - Liege Aguiar Pascoalino; Lillian Barros; João C.M. Barreira; M. Beatriz P. P. Oliveira; Filipa S. Reis (Food Structure, 2026)

Waves of innovation: The role of sustainability in driving impact in the blue economy – A PLS-SEM approach - Jennifer Nicole Elston; Hugo Emanuel dos Reis Sales da Cruz Pinto; Carla Filipa Sequeira Valente Nogueira (Marine Policy, 2026)

Corrigendum to “Urban trees through a functional traits’ lens: Exploring the interplay between tree functional groups and social-ecological factors” [Urban For. Urban Green. 107 (2025) 128749] - Filipa Grilo; Timon McPhearson; Cristiana Aleixo; Margarida Santos-Reis; Cristina Branquinho (Urban Forestry & Urban Greening, 2026)

Urban trees through a functional traits’ lens: Exploring the interplay between tree functional groups and social-ecological factors - Filipa Grilo; Timon McPhearson; Cristiana Aleixo; Margarida Santos-Reis; Cristina Branquinho (Urban Forestry & Urban Greening, 2025)

Earthworm abundance increases aggregate stability: A field study in a Mediterranean agroforestry system - Filipa Reis; Eduardo Nascimento; Cristina Cruz; Teresa Dias; Katarina Hedlund; María J.I. Briones; Matty P. Berg; José Paulo Sousa; Pedro Martins da Silva (Applied Soil Ecology, 2025)

Investigating bioactive compounds in apple pomace: Potential to develop high added-value products from an industrial surplus - Liege Aguiar Pascoalino; Tiane C. Finimundy; Tânia C.S.P. Pires; Carla Pereira; Lillian Barros; Isabel C.F.R. Ferreira; M. Beatriz P.P. Oliveira; João C.M. Barreira; Filipa S. Reis (Food Bioscience, 2025)

Cardiorespiratory and muscle oxygenation responses to voluntary hypoventilation at low lung volume in upper body repeated sprints - Cristóvão H. Rosa; Cristina P. Monteiro; Cláudia Barata; Mário C. Espada; Maria João Valamatos; André Bento; Ricardo J. Minhalma; Joana Filipa Reis (European Journal of Applied Physiology, 2024)
Purpose To investigate the impact of voluntary hypoventilation at low lung volumes (VHL) during upper body repeated sprints (RS) on performance, metabolic markers and muscle oxygenation in Brazilian Jiu-Jitsu (BJJ) athletes. Methods Eighteen male well-trained athletes performed two randomized RS sessions, one with normal breathing (RSN) and another with VHL (RS-VHL), on an arm cycle ergometer, consisting of two sets of eight all-out 6-s sprints performed every 30 s. Peak (PPO), mean power output (MPO), and RS percentage decrement score were calculated. Arterial oxygen saturation (SpO 2 ), heart rate (HR), gas exchange, and muscle oxygenation of the long head of the triceps brachii were continuously recorded. Blood lactate concentration ([La]) was measured at the end of each set. Bench press throw peak power (BP PP ) was recorded before and after the RS protocol. Results Although SpO 2 was not different between conditions, PPO and MPO were significantly lower in RS-VHL. $${\dot{\text{V}}}$$ V ˙ E , HR, [La], and RER were lower in RS-VHL, and VO 2 was higher in RS-VLH than in RSN. Muscle oxygenation was not different between conditions nor was its pattern of change across the RS protocol influenced by condition. [La] was lower in RS-VHL than in RSN after both sets. Conclusion Performance was significantly lower in RS-VHL, even though SPO 2 was not consistent with hypoxemia. However, the fatigue index was not significantly affected by VHL, nor was the neuromuscular upper body power after the RS-VHL protocol. Additionally, [La] was lower, and oxygen consumption was higher in RS-VHL, suggesting a higher aerobic contribution in this condition.

Where the not-so-wild things are in cities? The influence of social-ecological factors in urban trees at multiple scales - Filipa Grilo; Timon McPhearson; Alice Nunes; Cristiana Aleixo; Margarida Santos-Reis; Cristina Branquinho (Science of The Total Environment, 2024)

Assessment of the reproduction of six collembolan species in tropical soils naturally rich in potentially toxic elements - Gabriel Caixeta Martins; Filipa Alexandra de Ferreira Reis; Roberto Dall’Agnol; Sílvio Junio Ramos; Markus Gastauer; Tiago Natal-da-Luz; José Paulo Sousa; Luiz Roberto Guimarães Guilherme (Environmental Science and Pollution Research, 2024)

Lost and found: Patterns of marine litter accumulation on the remote Island of Santa Luzia, Cabo Verde - Diana Sousa-Guedes; Filipa Bessa; Alberto Queiruga; Leila Teixeira; Vitória Reis; José Alberto Gonçalves; Adolfo Marco; Neftalí Sillero (Environmental Pollution, 2024)

Milking the milk: Exploiting the full potential of milk constituents for nature-derived delivery systems - Filipa A. Soares; Beatriz Salinas; Salette Reis; Cláudia Nunes (Trends in Food Science & Technology, 2023)

Streams in the Mediterranean Region are not for mussels: Predicting extinctions and range contractions under future climate change - Janine P. da Silva; Ronaldo Sousa; Duarte Vasconcelos Gonçalves; Rafael Miranda; Joaquim Reis; Amílcar Teixeira; Simone Varandas; Manuel Lopes-Lima; Ana Filipa Filipe (Science of The Total Environment, 2023)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Alvarez waves in pregnancy: a comprehensive review - Sara Russo; Arnaldo Batista; Filipa Esgalhado; Catarina R. Palma dos Reis; Fátima Serrano; Valentina Vassilenko; Manuel Ortigueira (Biophysical Reviews, 2021)

Anesthesia for Stüve-Wiedemann syndrome: a rare adult patient case report - Vanessa Artilheiro; Filipa Portela; Ana Teresa Reis (Journal of Applied Genetics, 2020)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Integrated Procedure for Environmental Flow Assessment in Rivers - Francisco Godinho; Sérgio Costa; Paulo Pinheiro; Filipa Reis; António Pinheiro (Environmental Processes, 2014)

The annual cycle of spermatogenesis in Lipophrys pholis (Blenniidae), a recently proposed sentinel species for pollution monitoring - Filipa Ferreira; Miguel Machado Santos; Maria Armanda Reis-Henriques; Maria Natividade Vieira; Nuno Miguel Monteiro (Ichthyological Research, 2011)

Predator abundance in relation to small game management in southern Portugal: conservation implications - Pedro Beja; Luís Gordinho; Luís Reino; Filipa Loureiro; Margarida Santos-Reis; Rui Borralho (European Journal of Wildlife Research, 2009)

Modulation of branchial ion transport protein expression by salinity in glass eels (Anguilla anguilla L.) - Jonathan Mark Wilson; Alexandre Leitão; Ana Filipa Gonçalves; Catarina Ferreira; Patrick Reis-Santos; Ana-Violeta Fonseca; Joana Moreira da Silva; José Carlos Antunes; Cristina Pereira-Wilson; João Coimbra (Marine Biology, 2007)